Effectiveness of Project-Based Learning to Increase Students Learning Outcomes and Students Learning Activity on Electric Motors Installation at Vocational High School - Wardaningsih, Wardaningsih (Universitas Negeri Semarang, 2020)
This study aimed to see the effectiveness of the project-based learning model in improving learning outcomes and learning activities in the Electric Motor Installation subjects. This research was a research with a Quasi-Experiment approach. The research subjects were all students of class XI of the Department of Electricity at SMK N 5 Padang, which totaled 57 students. The study design used a non-equivalent control group design. The research subjects were class XI students of the Department of Electricity at SMK N 5 Padang by dividing the two groups as experimental groups and control groups. Data collection used test instruments and non-test instruments. Data analysis was carried out by descriptive and parametric analysis. The results obtained from this study can be concluded that the project-based learning model effectively improves learning outcomes and student learning activities in the Electric Motor Installation subjects.